PENGARUH MOTIVASI INTRINSIK, KOMUNIKASI, DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. BUTON MANDIRI PERDANA - Rais R, Muhammad; Rakhman, La Ode Abdul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The study aims to determine (1) The effect of intrinsic motivation on employee performance (2) The effect of communication on employee performance (3) The effect of financial compensation on employee performance. (4) The effect of intrinsic motivation, communication, and financial compensation simultaneously on employee performance. The data analysis method used is multiple regression analysis method, which is a statistical procedure in analysing the relationship between one or more independent variables on the dependent variable. The equation: Y=a+b1X1+b2X2+ b3X3+e. The results of the analysis concluded that (1) The first hypothesis (H1) is accepted and it is concluded that intrinsic motivation has a positive effect on employee performance. (2) The second hypothesis (H2) is accepted and it is concluded that communication has a positive effect on employee performance. (3) The third hypothesis (H3) is accepted and it is concluded that financial compensation has a positive effect on employee performance. (4) The fourth hypothesis (H4) is accepted and it is concluded that intrinsic motivation, communication and financial compensation together have a positive effect on employee performance